PROBLEMATIKA PERKEMBANGAN ANAK USIA DINI DI ERA DIGITAL DAN IMPLIKASINYA TERHADAP PEMBELAJARAN - Wina Susanti; Nurfarida Deliani; Juliana Batubara (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The rapid development of digital technology has brought about significant changes in the growth and development patterns of students. This study aims to examine the challenges facing student development in the digital age, identify the factors influencing it, explain the principles and laws of development, and understand the nature of humanity from an Islamic perspective as the foundation of holistic education. The study employs a qualitative approach using an integrative literature review of relevant primary and secondary sources. The findings indicate that uncontrolled use of technology has a negative impact on students’ concentration, social interaction, and emotional development. Additionally, biological, socio-economic, family environment, and cultural factors also influence the developmental process. Student development proceeds according to the principles of gradualism, individuality, and holism, and is influenced by maturity and experience. From an Islamic perspective, students are beings with inherent potential (fitrah) that must be developed in a balanced manner across the aspects of intellect, spirit, and body. The solutions offered include differentiated instruction, digital literacy, teacher-parent collaboration, and the integration of Islamic values into the learning process. This study contributes to the development of an integrative educational framework that combines modern pedagogical aspects with Islamic spiritual values.